Newton's law of motion - Leign, Richard; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2005)
Explain Newton's law of motion. It cover Newton's first law , or the law of inertia , as well as his second and third laws
Executive producer , Mark McAuliffe ; writer, Christine Henderson ; camera , Max Davis ; Michael Henry , Stephen French ; Sound , Wayne Martins ; editor , Paul Sutherland
Featuring : Chelsea Bruland
For senior secondary students
Keywords: Newton, Isaac, Sir, 1642 - 1727; Physics; Motion